Doxorubicin-loaded human serum albumin nanoparticles overcome transporter-mediated drug resistance in drug-adapted cancer cells - Onafuye, Hannah; Pieper, Sebastian; Mulac, Dennis; Jr., Jindrich Cinatl; Wass, Mark N.; Langer, Klaus; Michaelis, Martin (Beilstein Journal of Nanotechnology, 2019)
Resistance to systemic drug therapy is a major reason for the failure of anticancer therapies. Here, we tested doxorubicin-loaded human serum albumin (HSA) nanoparticles in the neuroblastoma cell line UKF-NB-3 and its ABCB1-expressing sublines adapted to vincristine (UKF-NB-3rVCR1) and doxorubicin (UKF-NB-3rDOX20). Doxorubicin-loaded nanoparticles displayed increased anticancer activity in UKF-NB-3rVCR1 and UKF-NB-3rDOX20 cells relative to doxorubicin solution, but not in UKF-NB-3 cells. UKF-NB-3rVCR1 cells were re-sensitised by nanoparticle-encapsulated doxorubicin to the level of UKF-NB-3 cells. UKF-NB-3rDOX20 cells displayed a more pronounced resistance phenotype than UKF-NB-3rVCR1 cells and were not re-sensitised by doxorubicin-loaded nanoparticles to the level of parental cells. ABCB1 inhibition using zosuquidar resulted in similar effects like nanoparticle incorporation, indicating that doxorubicin-loaded nanoparticles successfully circumvent ABCB1-mediated drug efflux. The limited re-sensitisation of UKF-NB-3rDOX20 cells to doxorubicin by circumvention of ABCB1-mediated efflux is probably due to the presence of multiple doxorubicin resistance mechanisms. So far, ABCB1 inhibitors have failed in clinical trials probably because systemic ABCB1 inhibition results in a modified body distribution of its many substrates including drugs, xenobiotics, and other molecules. HSA nanoparticles may provide an alternative, more specific way to overcome transporter-mediated resistance.
Keywords: ABCB1; cancer; doxorubicin; drug resistance; human serum albumin; nanoparticles; transporter

Cancer Fact Sheets - International Agency for Research on Cancer

(untitled) - Holohan, C.; Van Schaeybroeck, S.; Longley, D. B.; Johnston, P. G. (Nat. Rev. Cancer, 2013)

(untitled) - Steeg, P. S. (Nat. Rev. Cancer, 2016)

(untitled) - Siegel, R. L.; Miller, K. D.; Jemal, A. (Ca-Cancer J. Clin., 2018)

(untitled) - Robey, R. W.; Pluchino, K. M.; Hall, M. D.; Fojo, A. T.; Bates, S. E.; Gottesman, M. M. (Nat. Rev. Cancer, 2018)

(untitled) - Bar-Zeev, M.; Livney, Y. D.; Assaraf, Y. G. (Drug Resist. Updates, 2017)

(untitled) - Thierry, A. R.; Vigé, D.; Coughlin, S. S.; Belli, J. A.; Dritschilo, A.; Rahman, A. (FASEB J., 1993)

(untitled) - Bennis, S.; Chapey, C.; Robert, J.; Couvreur, P. (Eur. J. Cancer, 1994)

(untitled) - Wong, H. L.; Bendayan, R.; Rauth, A. M.; Xue, H. Y.; Babakhanian, K.; Wu, X. Y. (J. Pharmacol. Exp. Ther., 2006)

(untitled) - Prados, J.; Melguizo, C.; Ortiz, R.; Velez, C.; Alvarez, P. J.; Arias, J. L.; Ruiz, M. A.; Gallardo, V.; Aranega, A. (Anti-Cancer Agents Med. Chem., 2012)

(untitled) - Oliveira, M. S.; Aryasomayajula, B.; Pattni, B.; Mussi, S. V.; Ferreira, L. A. M.; Torchilin, V. P. (Int. J. Pharm., 2016)

(untitled) - Maiti, C.; Parida, S.; Kayal, S.; Maiti, S.; Mandal, M.; Dhara, D. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Weber, C.; Kreuter, J.; Langer, K. (Int. J. Pharm., 2000)

(untitled) - Langer, K.; Balthasar, S.; Vogel, V.; Dinauer, N.; von Briesen, H.; Schubert, D. (Int. J. Pharm., 2003)

(untitled) - Langer, K.; Anhorn, M. G.; Steinhauser, I.; Dreis, S.; Celebi, D.; Schrickel, N.; Faust, S.; Vogel, V. (Int. J. Pharm., 2008)

(untitled) - Dreis, S.; Rothweiler, F.; Michaelis, M.; Cinatl, J., Jr; Kreuter, J.; Langer, K. (Int. J. Pharm., 2007)

(untitled) - von Storp, B.; Engel, A.; Boeker, A.; Ploeger, M.; Langer, K. (J. Microencapsulation, 2012)

(untitled) - Ferrer, R.; Mateu, X.; Maseda, E.; Yébenes, J. C.; Aldecoa, C.; De Haro, C.; Ruiz-Rodriguez, J. C.; Garnacho-Montero, J. (Expert Rev. Clin. Pharmacol., 2018)

(untitled) - Elzoghby, A. O.; Samy, W. M.; Elgindy, N. A. (J. Controlled Release, 2012)

(untitled) - Kotchetkov, R.; Driever, P.; Cinatl, J.; Michaelis, M.; Karaskova, J.; Blaheta, R.; Squire, J.; Von Deimling, A.; Moog, J.; Cinatl, J., Jr (Int. J. Oncol., 2005)

(untitled) - Szakács, G.; Paterson, J. K.; Ludwig, J. A.; Booth-Genthe, C.; Gottesman, M. M. (Nat. Rev. Drug Discovery, 2006)

(untitled) - Michaelis, M.; Rothweiler, F.; Klassert, D.; von Deimling, A.; Weber, K.; Fehse, B.; Kammerer, B.; Doerr, H. W.; Cinatl, J., Jr (Cancer Res., 2009)

(untitled) - Michaelis, M.; Rothweiler, F.; Löschmann, N.; Sharifi, M.; Ghafourian, T.; Cinatl, J., Jr (Oncotarget, 2015)

(untitled) - Carter, D. C.; Ho, J. X. (Adv. Protein Chem., 1994)

(untitled) - Kavallaris, M. (Nat. Rev. Cancer, 2010)

(untitled) - Wijdeven, R. H.; Pang, B.; Assaraf, Y. G.; Neefjes, J. (Drug Resist. Updates, 2016)

(untitled) - Wischke, C.; Schwendeman, S. P. (Int. J. Pharm., 2008)

(untitled) - Tyler, B.; Gullotti, D.; Mangraviti, A.; Utsuki, T.; Brem, H. (Adv. Drug Delivery Rev., 2016)

(untitled) - Pieper, S.; Onafuye, H.; Mulac, D.; Cinatl, J., Jr; Wass, M. N.; Michaelis, M.; Langer, K. (bioRxiv, Pharmacol. Toxicol., 2018)

(untitled) - Merlot, A. M.; Kalinowski, D. S.; Richardson, D. R. (Front. Physiol., 2014)

(untitled) - Hyun, H.; Park, J.; Willis, K.; Park, J. E.; Lyle, L. T.; Lee, W.; Yeo, Y. (Biomaterials, 2018)

(untitled) - Brufsky, A. (Exp. Hematol. Oncol., 2017)

(untitled) - Vallo, S.; Köpp, R.; Michaelis, M.; Rothweiler, F.; Bartsch, G.; Brandt, M. P.; Gust, K. M.; Wezel, F.; Blaheta, R. A.; Haferkamp, A.; Cinatl, J., Jr (Oncol. Lett., 2017)

(untitled) - Sanson, C.; Schatz, C.; Le Meins, J.-F.; Soum, A.; Thévenot, J.; Garanger, E.; Lecommandoux, S. (J. Controlled Release, 2010)

(untitled) - Fletcher, J. I.; Ziegler, D. S.; Trahair, T. N.; Marshall, G. M.; Haber, M.; Norris, M. D. (Nat. Rev. Cancer, 2018)

(untitled) - Michaelis, M.; Rothweiler, F.; Barth, S.; Cinatl, J.; van Rikxoort, M.; Löschmann, N.; Voges, Y.; Breitling, R.; von Deimling, A.; Rödel, F.; Weber, K.; Fehse, B.; et al. (Cell Death Dis., 2011)

The Resistant Cancer Cell Line (RCCL) collection - University of Kent

(untitled) - Mosmann, T. (J. Immunol. Methods, 1983)

(untitled) - Michaelis, M.; Matousek, J.; Vogel, J.-U.; Slavik, T.; Langer, K.; Cinatl, J.; Kreuter, J.; Schwabe, D.; Cinatl, J., Jr (Anti-Cancer Drugs, 2000)